Management of Tennis Elbow with sodium hyaluronate periarticular injections - Petrella, R. J.; Cogliano, A.; Decaria, J.; Mohamed, N.; Lee, R. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2010)
Objectives To determine the efficacy and safety of peri-articular hyaluronic acid injections in chronic lateral epicondylosis (tennis elbow).